2013
DOI: 10.5114/ninp.2013.38223
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of falls in Parkinson disease: prospective study

Abstract: Falls in PD patients occurred three times more frequently than in controls. Independent risk factors for falls were: high score in FOG-Q, older age and presence of falls in medical history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…A high score in the Freezing of Gait Questionnaire, older age, and the presence of falls in medical history are independent risk factors for falls [50]. We found that the reduction in falls was greater after a long-term (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…A high score in the Freezing of Gait Questionnaire, older age, and the presence of falls in medical history are independent risk factors for falls [50]. We found that the reduction in falls was greater after a long-term (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…Falls occur in approximately 50% of persons with PD, of which about 30% are injurious. 11,12 Postural instability has been identified as an independent predictor of falls in persons with PD, 13,14 and around one third of falls are caused by an unstable posture. 15 Current evidence suggests that PI is poorly responsive to general treatment options in persons with PD, such as medication with L-dopa and deep brain stimulation 16 ; some domains of balance dysfunction even worsen under pharmacological and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The concomitant presence of classical gait dysfunction and dementia may increase the risk of falls in patients with PD, resulting in a worse outcome and increased hospitalisations 10 11. Considering that the prevalence of dementia in patients with PD reaches about 80% after 20 years and the ageing per se is one of the main risk factors for falls,12 specific treatments to interfere with the cholinergic and dopaminergic imbalance may improve the long-term outcome of patients with PD 13…”
Section: Introductionmentioning
confidence: 99%